Enhancing ice slurry generation by using inclined cavity for subzero cold thermal energy storage: Simulation, experiment and performance analysis. (15th September 2019) - Tiwari, Vipul Kumar; Kumar, Alok; Kumar, Arvind
Abstract: Ice slurry generation is an important stage in ice slurry-based cold thermal energy storage systems. Predictive modelling and simulation of ice slurry generation requires consideration of solidification of an aqueous solution along with multiphase convection. Towards enhancing the generation, this work numerically and experimentally investigates ice slurry generation in an inclined cavity. The inclined cavity provides a driving shear force for ice slurry generation from the mushy zone. A model considering solidification, multiphase convection, interfacial drag and sedimentation is used to simulate the flow field, temperature, species and solid fraction distribution. Solidification experiments of ice slurry generation are performed. The experiments are equipped with Particle Image Velocimetry, high resolution imaging and thermocouples to measure real-time flow field, solidified and mushy zone thickness and local temperature. Experimental and predicted solid fraction distribution, velocity field, solidified and mushy zone thickness, mass of ice slurry and temperature variation have been compared. After validations, the effect of process parameters, such as cavity inclination angle, solute initial concentration and Stefan number on performance of ice slurry generation is delineated. The performance is determined by various indicators, such as mass of ice slurry produced, cold energy stored by the ice slurry and system's effectiveness. Highlights: This paper proposes a non-conventional method of improving ice slurry generation. Physical phenomena in an inclined ice slurry generator are numerically studied. Experimental techniques are also used to measure the fluid flow and ice fraction. Evolution of ice fraction, species, temperature and drift velocity is discussed. Thermal performance of the inclined generator is delineated.